Identifikasi Elemen Resin Komposit Mikrohibrid dan Nanohibrid dengan Energy Dispersive X-ray dan Gambaran Mikrostruktur dengan Scanning Electrone Microscopy - Kholidina Imanda Harahap; Harry Agusnar; Sumadhi S (Jurnal Material Kedokteran Gigi, 2012)
Microhybrid and nanohybrid composite resins are an esthetical restoration materials which having silica as filler material for improving physical, mechanical and optical properties. Elements contained in composite resin influence its properties. The aims of this investigation are to identify the elements and microstructure images of microhybrid and nanohybrid composite resin by using energy dispersive x-ray (EDX) and scanning electrone microscope (SEM). Microhybrid (Solare F, Japan) and nanohybrid (Brilliant G, Switzerland) composite resin are used in this study. Samples is build in tablet shape with 15 mm of diameter and 1 mm of thick and were polymerized at 2 mm cone distance and 20 s curing time by using visible blue light curing unit (Litex 2000, China). Sample then is prepared for SEM and EDX investigations to found out microstructure images and elements contained. Microstructure images show the distribution of filler particle in microhybrid composite resin more wide apart than nanohybrid composite resin. By using EDX C, O, Al, Si, Na, F, and In are found out in microhybrid composite resin and C, O, Al, Si and Ti in nanohybrid composite resin with different weight percentages in both of composite resin respectively.